2017
DOI: 10.1042/bsr20171049
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy attenuates endothelial-to-mesenchymal transition by promoting Snail degradation in human cardiac microvascular endothelial cells

Abstract: Endothelial-to-mesenchymal transition (EndMT) mainly exists in cardiovascular development and disease progression, and is well known to contribute to cardiac fibrosis. Recent studies indicated that autophagy also participates in the regulation of cardiac fibrosis. However, the precise role of autophagy in cardiac fibrosis and the underlying molecular mechanism remain unclear. The present study aimed to explore the role of autophagy in EndMT, reveal the underlying molecular mechanism, and seek new therapy for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 42 publications
(49 reference statements)
0
33
0
Order By: Relevance
“…Importantly, SNAI1 is degraded through SQSTM1-dependent autophagy, demonstrating a direct mechanism of autophagy-mediated regulation of EMT [164]. In support of this, autophagy-mediated degradation of SNAI1 reduces hypoxia-induced EMT in human cardiac microvascular endothelial cells (HCMECs) [165]. In contrast, starvationinduced autophagy activates EMT and is required for HepG2 and BEL7402 HCC cell invasion in vitro [166].…”
Section: Autophagy Regulates Emtmentioning
confidence: 84%
“…Importantly, SNAI1 is degraded through SQSTM1-dependent autophagy, demonstrating a direct mechanism of autophagy-mediated regulation of EMT [164]. In support of this, autophagy-mediated degradation of SNAI1 reduces hypoxia-induced EMT in human cardiac microvascular endothelial cells (HCMECs) [165]. In contrast, starvationinduced autophagy activates EMT and is required for HepG2 and BEL7402 HCC cell invasion in vitro [166].…”
Section: Autophagy Regulates Emtmentioning
confidence: 84%
“…Defects in mitophagy, a selective form of autophagy that specifically removes dysfunctional mitochondria from cells has also been implicated in AMD pathogenesis [116]. In cancer studies, the activation of autophagy, mitophagy and impaired mitochondrial functionality have been linked to both EMT [117] and EndMT [118], warranting further research into whether parallels exist for RPE and CECs.…”
Section: Metabolic Dysfunction and Autophagy In Amdmentioning
confidence: 99%
“…Under hypoxic conditions, the EndMT of human cardiac microvascular ECs promoted tube formation. Autophagy provides protective effects against the EndMT of human cardiac microvascular ECs by degrading Snail under hypoxic conditions 51 . In addition, it has been suggested that hypoxia induces EndMT in human coronary ECs via Hif1a-activated Snail, indicating that endocardium-derived ECs undergo EndMT 23 .…”
Section: Role Of Oxidative Stress and Hypoxia In Endmtmentioning
confidence: 99%